A comprehensive pan-cancer analysis of the expression characteristics, prognostic value, and immune characteristics of TOP1MT - Fei, Lihong; Lu, Zhimin; Xu, Yufen; Hou, Guoxin (Frontiers in Genetics, 2022)
Background: Mitochondria are the central hub of several metabolic pathways that not only provide a lot of energy for normal cell growth but also play a crucial role in tumor cell growth and survival. Mitochondrial topoisomerase I (TOP1MT) is a type IB topoisomerase found in mitochondria of vertebrates. There is, however, no pan-cancer analysis of TOP1MT. The present study aims to explore TOP1MT expression in pan-cancer tissues and identify whether it can be used as a target for mitochondrial anticancer therapy. Methods and results: The original TOP1MT expression data in 33 different types of cancer patients were obtained from the TCGA and GTEx databases. TOP1MT is highly expressed in cancer tissues, including BLCA, BRCA, CHOL, COAD, DLBC, ESCA, GBM, HNSC, KIRC, KIRP, LGG, LIHC, LUAD, LUSC, PAAD, PCPG, PRAD, READ, SKCM, STAD, THYM, UCEC, and UCS. Kaplan-Meier survival curve analysis revealed an association of high TOP1MT expression in BLCA, HNSC, KIRP, PAAD, UCEC, and LIHC cancer tissues with poor prognosis of cancer patients, including poor OS, DSS, and PFI. Linkedomics analysis demonstrated a positive correlation of TOP1MT expression with CNA and a negative correlation with methylation. The expression of TOP1MT was found to be significantly correlated with immune cells and immune checkpoints in the TIMER database. Functional analysis revealed a close relationship between TOP1MT expression and ribosome. Conclusion: TOP1MT will be investigated further as a biomarker for mitochondrial anticancer therapy and cancer immunotherapy. As such, TOP1MT will be investigated further as a biomarker for mitochondrial anticancer therapy and cancer immunotherapy.